The Activities of the Indicative Organization of ARF Dashnaksutyun in the Months after the Vitosh Disaster (from March to mid-July, 1905) - Grigoryan, Hovik (History and Culture, 2021)
The activities of the Indicative Organization of ARF Dashnakstutyun of Constantinople in the months after the Vitosh disaster (1905 March to mid-July) aimed towards finalization of the organization of assassination of the Bloody Sultan Abdul Hamid II ("The Case of Nzhuyk") are comprehensively analyzed in the current publication. A number of episodes from the activities of the Responsible-Indicative Organization of ARF Dashnakstutyun of Constantinople (almost left out of the historians’ sight due to various reasons in the past) are presented in detail based on various sources, including documents from ARF Dashnakstutyun’s Boston central archive published for the first time during the last decades. Based on combined analysis of often contradicting and mutually excluding factual materials, the current publication gives exhaustive answers to several questions which are still debatable nowadays. Particularly, the current publication presents the objective and subjective factors that made the Indicative Organization abandon its preliminary plan after the martyrdom of its leader Kristapor Mikayelyan and choose new tactics of striking the decisive blow during the last stages of the preparation of "The Case of Nzhuyk". The current publication also makes important adjustments on the activities of the Indicative Organization of ARF Dashnakstutyun, as well as several controversial and contradictory issues on "The Case of Nzhuyk" for historians.